Neighbour noise annoyance is associated with various mental and physical health symptoms: results from a nationwide study among individuals living in multi-storey housing - Heidi A. R. Jensen; Birgit Rasmussen; Ola Ekholm (BMC, 2019)
Abstract Background Noise exposure is considered a stressor that may potentially exert negative health effects among the exposed individuals. On a population basis, the most prevalent and immediate response to noise is annoyance, which is an individually experienced phenomenon that may activate physiological stress-responses and result in both physical and mental symptoms. Health implications of traffic noise have been investigated thoroughly, but not of neighbour noise. The aim of the present study was to examine the associations between neighbour noise annoyance and eight different physical and mental health symptoms. Methods Cross-sectional data from the Danish Health and Morbidity Survey 2017 were used. The present study included a random sample of 3893 adults living in multi-storey housing. Information on neighbour noise annoyance and various health symptoms (e.g. pain in various body parts, headache, sleeping problems, depression, and anxiety) during the past two weeks was obtained by self-administered questionnaires. The question on neighbour noise annoyance and health symptoms, respectively, had three possible response options: 'Yes, very annoyed/bothered', 'Yes, slightly annoyed/bothered', 'No'. The associations between neighbour noise annoyance and very bothering physical and mental health symptoms were investigated using multiple logistic regression models. Results Being very annoyed by neighbour noise was significantly associated with higher odds of being very bothered by all eight health symptoms (adjusted OR = 1.73-3.32, all p-values < 0.05) compared to individuals not annoyed by noise from neighbours. Statistically significant interactions were observed between sex and two of the eight health symptoms. Among women, a strong association was observed between neighbour noise annoyance and being very bothered by pain or discomfort in the shoulder or neck, and in the arms, hands, legs, knees, hips or joints. Among men, no associations were observed. Conclusions Based on the findings from this study, neighbour noise annoyance is strongly associated with eight different physical and mental health symptoms. Future studies are encouraged to 1) determine the direction of causality using a longitudinal design, 2) explore the biological mechanisms explaining the sex-specific impact of neighbour noise annoyance on symptoms of musculoskeletal pain or discomfort and the other outcomes as well.